Clifford's sports day - Bridwell, Norman (New York : Scholastic, 1996)
Clifford goes to school with Emily Elizabeth to participate in the outdoor sports day activities.
360
Keywords: Dogs -- Fiction; SportsvxFiction; Contests -- Fiction; Schools -- Fiction